Opioid Replacement for Pregnant Mothers With Opioid Use Disorder and Fetal Neurodevelopment: A Review - Caragh Dallas Miller; Elizabeth Nizalik; David Grynspan (University of Ottawa Journal of Medicine, 2017)
This paper reviews the published literature regarding neurodevelopmental outcomes in neonates following in utero exposure to opioids. We have summarized available clinical and experimental data. Overall, clinical data is limited and equivocal with most studies showing no significant neurodevelopmental impairments in infants and children exposed to opioids in utero. Various outcome measures assessed language, communication, cognitive, psychomotor, and behavioural outcomes. The equivocality of the data may be a result of the complexity of the cohort and the inability to disentangle the effect of the opioids from the multiple comorbidities. Results from experimental data show that all opioids cross the placental barrier. Mouse studies show biochemical and neurophysiological changes, leading to long-term effects on learning and memory. Some data also suggests that epigenetic and imprinting changes in the central nervous system of mice may lead to multigenerational effects of opioid exposure. Ultimately, the benefits of opioid replacement therapy outweigh its risks, but it should be done in the context of a broader biopsychosocial risk reduction approach. Promoting mother-child bonding and care through skin-to-skin contact, rooming-in, and breastfeeding can reduce severity of neonatal abstinence syndrome and improve outcomes. This cohort of women and children requires advocacy for comprehensive multidisciplinary care.